The experienced energyscape of an energy transition: A case study of the peat transition in Northern Finland - Lempinen, Hanna (Alue ja Ympäristö, 2023)
Warming climate and the limits of planetary boundaries are forcing societies to seek pathways towards low-carbon and more environmentally futures. In this process, energy-related transitions play a crucial role. However, energy transitions themselves are bound to pose manifold justice and sustainability challenges that will vary across different sociocultural and geographical settings. This article focuses on one such transition – Finland's phase-out of energy peat – and the ways in which its impacts have been experienced by those whose livelihoods depend on peat extraction. Through the theory-method framework of situational analysis and against the backdrop of scholarly literature on just energy transitions, sociocultural meanings of (fossil) livelihoods and the notion of energyscape, this article makes use of participatory ethnographic research and interview materials gathered in Northern Finland with the aim to grasp the ways in which peat as a livelihood permeates the lives of those engaged in its extraction. The conclusions of the article both highlight the manifold meanings that livelihoods have for those who practice them and render visible the concrete shortcomings of Finland’s peat transition policies. The results of the article can support planning more inclusive and targeted transition policies for future livelihood transitions that inevitably lie ahead. Ilmastonmuutos ja planeetan kantokyvyn rajat vaativat yhteiskuntia siirtymään nopealla tahdilla kohti vähähiilisempiä ja ympäristön kannalta kestävämpiä olemisen tapoja. Tämän tavoitteen saavuttamisessa energiasiirtymillä on keskeinen rooli. Energiasiirtymät itsessään kuitenkin asettavat yhteiskunnille uusia haasteita ratkaistavaksi, joista keskeisimmät liittyvät siihen, miten siirtymät on mahdollista toteuttaa paitsi taloudellisesti kestävästi myös sosiaalisesti hyväksyttävästi ja oikeudenmukaisesti. Tässä artikkelissa keskityn tarkastelemaan suomalaisen turvealan oikeudenmukaisen siirtymän toimeenpanon kokemuksia ja niiden vaikutuksia suomalaisen ...